NILAI EKONOMI BENTENG ROTTERDAM DAN MUSEUM LA GALIGO KOTA MAKASSAR: APLIKASI TRAVEL COST DAN CONTINGENT VALUATION METHOD - , Muhammad Azwar Waris ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aimed to estimate the economic value of Fort Rotterdam and La Galigo Museum. The economic valuation of Fort Rotterdam and La Galigo Museum was the travel cost method and contingent valuation aplication by using the visitors individual data. Sample used both for travel cost and contingent valuation method was 115 visitors. Factors that influenced the number of visits to the Fort Rotterdam and La Galigo Museum are travel cost, income, and education. Factors that influenced the individual willingness to pay for the Fort Rotterdam are travel cost, income, age, education, and substitute. The individual willingness to pay for La Galigo Museum are influenced by travel cost, income, age, education, and substitute. The consumer surplus result for travel cost method was Rp1.029.601,03 â Rp7.505.791,50. The willingness to pay of the Fort Rotterdam visitors was Rp3.400,00, and for the La Galigo Museum was Rp10.700,00. The economic value interval of Fort Rotterdam and La Galigo Museum using travel cost method was Rp41.716.344.933,00 â Rp304.112.154.206,00. The economic value of Fort Rotterdam using contingent valuation method was Rp137.757.800,00. The economic value of La Galigo Museum using the same method was Rp258.169.600,00.